OPTIMIZING FACILITIES AND INFRASTRUCTURE IN SCIENCE LEARNING: CHALLENGES, OPPORTUNITIES, AND SOLUTIONS THROUGH EBOOKS, LEARNING VIDEOS, LABORATORIES, AND TEACHING AIDS - Nur Almi; Margaretha Dhera; Moh. Risqa; Febri Riansah; Marungkil Pasaribu (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2025)
This study presents a literature-based analysis focusing on the procurement and optimization of educational facilities and infrastructure, particularly in the context of science education. To improve the efficiency and efficacy of the teaching and learning process, the research attempts to identify important issues and offer workable solutions pertaining to the use of eBooks, instructional videos, labs, and teaching aids. Even though infrastructure and facilities are essential to a quality education, science courses are not making the most of them due to issues like inadequate digital resources, subpar lab equipment, and a lack of instructional media. The results demonstrate that maximizing the infrastructure for science education necessitates a multipronged strategy that includes the incorporation of suitable educational technologies, the supply of practical teaching tools, and ongoing professional development for teachers. Furthermore, to guarantee fair access and the long-term viability of educational resources, government participation through encouraging policies and consistent investment is essential. By tackling these issues, science instruction can become more dynamic, captivating, and capable of generating students who are competent and scientifically literate.